Transhepatic left ventricular only pacing after left bundle branch area pacing attempt with high pacing threshold - Korkmaz, Ahmet; Özdemir, Mustafa; Ertunç Açıkgöz, Gözde; Mavioğlu, Levent; Can, İrem Dilara; Kara, Meryem; Özcan Çetin, Hande Elif; Özeke, Özcan; Çay, Serkan; Özcan, Fırat; Özoğul, Yusuf Bayram; Aras, Dursun; et al. (NLM (Medline), 2023)
A 50-year-old male with a permanent dual chamber pacemaker (DDD) 23 years ago was referred for a rapid increase in right ventricular (RV) pacing impedance. His left ventricular (LV) ejection fraction was 45%. Since the patient was pacemaker-dependent, the insertion of a new RV lead was planned. However, the venography and imaging studies revealed both left and right subclavian veins to be occluded/non-accessible. We failed also to cross the lesion by percutaneous approach. Then, we planned the extraction procedure as a first stage with the thought that it can provide a new venous route via extraction sheath; however, the patient did not accept the procedure as its high risk. Therefore, the surgical epicardial LV lead was implanted and connected to the left subpectoral pocket by using the previous functional right atrial (RA) lead for DDD pacing. Unfortunately, 1 month later, the patent presented with a left-sided pocket infection, and we had to remove all endocardial RA and RV leads using the lead extraction system. We could not again pass the calcified superior vena cava despite the successful lead extraction. Due to an active pocket infection, the surgically placed pacemaker was removed from the skin leaving the epicardial LV lead in place to remove or drain the infected fluid. A leadless pacemaker was an option, but due to financial constraints could not be done for this patient. The femoral venous access could not be taken due to the non-availability of 69 cm RV lead. The hepatic vein was the only available access to implant a DDD pacemaker.
Keywords: High Pacing Threshold; Area Pacing Attempt; Ventricular Pacing